Дуальна природа капіталу і принцип додатковості: загальноекономічний та обліковий аспекти - Задніпровський, О.Г. (Культура народов Причерноморья, 2014)
В статті розглянуто історичний аспект формування поглядів теоретиків–економістів та
обліковців щодо категорії «капітал». Простежено комплекс підходів до визначення сутнісної
характеристики цього поняття – в аспекті тлумачення його змісту в інтересах бухгалтерського
обліку, – як елементу активу або пасиву. Акцентовано увагу на однобокість будь–якої окремо взятої
дефініції капіталу та обґрунтовано можливість адекватного розкриття сутнісного наповнення змісту
терміна із застосуванням принципу додатковості. В статье рассмотрен исторический аспект формирования взглядов теоретиков –
экономистов и учетчиков касательно категории «капитал». Рассмотрен комплекс подходов к
определению сущностной характеристики этого понятия–в аспекте толкования его содержания в
интересах бухгалтерского учета, – как элемента актива или пассива. Акцентировано внимание на
однобокость любой отдельно взятой дефиниции капитала и обоснована возможность адекватного
раскрытия сущностного наполнения содержания термина с применением принципа дополнительности. The article deals with the historical aspect of shaping the views of theorists, economists and
accountants with respect to the category of " capital ." Investigated the genesis of forming views on capital as
self–rising cost – ranging from interpretations of medieval thinkers, classical political economy and theory of
accounting XVIII–XIX centuries. and the views of scientists and regulatory documents in keeping our days. It
traces the complex approach to defining the essential characteristics of this concept – in terms of the
interpretation of its content for the benefit of accounting, as part of an asset or liability within the two major
accounting and economic concepts – physical and financial. Identification of practical contradiction in the
definition of a term "capital", depending on the context of application, essentially different, and the complexity
of the dual objects exhaustive definition within a certain period of difficult concepts. Attention is focused on any
one–sidedness of a single definition of capital and the opportunity to reasonably adequate disclosure of the
essential content of the content of the term by applying the principle of subsidiarity, which allows to characterize
the phenomena and objects using features that are mutually exclusive .